Light-induced damage to photosystem II at a very low temperature (195 K) depends on singlet oxygen - Mattila Heta; Tyystjärvi Esa (WILEY, 2025)
Photosynthetic organisms, like evergreen plants, may encounter strong light at low temperatures. Light, despite being the energy source of photosynthesis, irreversibly damages photosystem II (PSII). We illuminated plant thylakoid membranes and intact cyanobacterial cells at -78.5? and assayed PSII activity with oxygen evolution or chlorophyll fluorescence, after thawing the sample. Both UV radiation and visible light damaged PSII of pumpkin (Cucurbita maxima) thylakoids at -78.5?, but visible-light-induced photoinhibition at -78.5?, unlike at +20?, proceeded only in the presence of oxygen. A strong magnetic field that would decrease triplet chlorophyll formation by recombination of the primary radical pair slowed down photoinhibition at -78.5?, suggesting that singlet oxygen produced via recombination of the primary pair is a major contributor to photoinhibition at -78.5?. However, a magnetic field did not affect singlet oxygen production at +25?. Thylakoids of winter leaves of an evergreen plant, Bergenia, were less susceptible to photoinhibition both at -78.5? and +20?, contained high amounts of carotenoids and produced little singlet oxygen (measured at +20?), compared to thylakoids of summer leaves. In contrast, high carotenoid amount and low singlet oxygen yield did not protect a Synechocystis mutant from photoinhibition at -78.5?. Thylakoids isolated from Arabidopsis thaliana grown under high light, which reduces PSII antenna size, were more resistant than control plants against photoinhibition at -78.5? but not at +20?, although carotenoid amounts were similar. The results indicate that visible-light-induced photoinhibition at -78.5? depends on singlet oxygen, whereas photoinhibition at +20? is largely independent of oxygen.